Analysis of the Influence of Knowledge About Intellectual Property Rights Waqf, Religion, and Mandate on Nadzir on Interests in Intellectual Property Rights Waqf in East Jakarta City - Muhammad Faiz Haikal; Nurizal Ismail (Department Islamic Economics, 2023)
The objective of this study is to analyse a public understanding of intellectual property rights waqf, religiosity, and trust in Nadzir on the intention in intellectual property rights waqf. To get the finding, the quantitative analysis is performed using SEM-PLS and quantitative analysis with 100 respondents in East Jakarta. Waqf is a good investment for all human life. Intellectual property rights waqf is a component of movable object waqf, along with cash waqf. The conclusion for this research is knowledge and trust to nadzhir have a significant positive influence on interest in IPR waqf with and religiosity does not have positive influence because the P – Value is above of significancy 10% (0.10). This research contributes to understanding dynamics of IPR waqf and provides insight for stakeholder involved in waqf management and development that improve the the literacy of public and skill of nadzhir regarding IPR waqf.